Predicting death from surgery for lung cancer: a comparison of two scoring systems in two European countries - O'Dowd, Emma L.; Lüchtenborg, Margreet; Baldwin, David R.; McKeever, Tricia M.; Powell, Helen A.; Møller, Henrik; Jakobsen, Erik; Hubbard, Richard B. (Elsevier, 2016)
Objectives: Current British guidelines advocate the use of risk prediction scores such as Thoracoscore to estimate mortality prior to radical surgery for non-small cell lung cancer (NSCLC). A recent publication used the National Lung Cancer Audit (NLCA) to produce a score to predict 90 day mortality (NLCA score). The aim of this study is to validate the NLCA score, and compare its performance with Thoracoscore.